2013
DOI: 10.1111/j.1521-0391.2013.12012.x
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Pathways to Alcohol-Related Problems

Abstract: These results indicate that the A1+ allele may link alexithymia and prior emotional abuse to a higher risk for substance-based coping and subsequent alcohol problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…For example, in a sample of youth recruited from battered women’s shelters and the general community, childhood sexual abuse has been found to increase the likelihood that girls aged 13-19 will eventually use substances, even after controlling for family dysfunction, maternal substance use, and other internalizing problems (depression and anxiety) (Bailey & McCloskey, 2005). Several studies have suggested emotional abuse as a risk factor for substance use (Highland, Herschl, Klanecky, & McChargue, 2013; Moran et al, 2004; Norman, Byambaa, De, Butchart, Scott, & Vos, 2012). For example, in a retrospective study of adults, Dube and colleagues (2006) found that childhood emotional abuse was associated with 2.5 times higher odds of initiating alcohol use during earlyadolescence .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a sample of youth recruited from battered women’s shelters and the general community, childhood sexual abuse has been found to increase the likelihood that girls aged 13-19 will eventually use substances, even after controlling for family dysfunction, maternal substance use, and other internalizing problems (depression and anxiety) (Bailey & McCloskey, 2005). Several studies have suggested emotional abuse as a risk factor for substance use (Highland, Herschl, Klanecky, & McChargue, 2013; Moran et al, 2004; Norman, Byambaa, De, Butchart, Scott, & Vos, 2012). For example, in a retrospective study of adults, Dube and colleagues (2006) found that childhood emotional abuse was associated with 2.5 times higher odds of initiating alcohol use during earlyadolescence .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated relationships between substance abuse and deficits in discrete components of metacognition, such as the ability to name and express one’s own emotions (a condition known as alexithymia; e.g., Thorberg, Young, Sullivan, & Lyvers, 2009). In a more recent study, Highland, Herschl, Klanecky, and McChargue (2013) found that in persons with a specific gene expression, greater levels of alexithymia were associated with greater levels of substance abuse, and Lysaker et al (2014) found that low metacognitive mastery—the ability to use mental states to solve social problems—moderated the effects of alexithymia in persons with substance-abuse problems. In addition, metacognitive deficits have been linked to poorer outcomes in substance-abuse recovery (Saladin et al, 2012; Thorberg et al, 2011), deliberate self-harm (Verrocchio, Conti, & Fulcheri, 2010), and emotional distress (De Rick, Vanheule, & Verhaeghe, 2009) as well as more excessive use of alcohol in nonclinical samples (Lyvers, Onuoha, Thorberg, & Samios, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals who respond in a consistently avoidant way have been found to be vulnerable to problematic gaming [ 31 ] and other addictive behaviors, such as binge drinking, excessive eating, and smoking [ 32 , 33 , 34 ]. Moreover, individuals who had the DRD2 Taq1 A1 allele and experienced extreme emotional stress were likely to choose more avoidant coping methods than non-carriers, thus increasing the severity of alcohol abuse [ 35 ].…”
Section: Introductionmentioning
confidence: 99%